Pocket welding guide : a guide to better welding. (Hobart Institute of Welding Technology, 2010)
Known as the "Welder's Bible", this book covers a wide variety of subjects essential for students and of interest to the veteran welders and other professionals.
"EW609."
Includes index.
Keywords: Welding -- Handbooks, manuals, etc.; elektronické knihy; electronic books